2021
DOI: 10.3389/fneur.2021.675050
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Wu Qin Xi Exercise on Response Inhibition and Cortical Connectivity in Parkinson's Disease: Design and Implementation of a Randomized Controlled Clinical Trial

Abstract: Background: Motor symptom disorders in patients with Parkinson disease (PD) are closely related to reduced inhibitory ability. Although exercise has been shown to improve this ability in patients with PD, its effects on proactive and reactive inhibition have not been determined. Most previous studies of inhibitory control disorder in people with PD have been behavioral, and little attention has been paid to functional cortical connectivity. Wu Qin Xi, a low–medium-intensity qigong exercise that is safe and eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…As mind-body therapies that originated in China, TCEs play an important role in complementary and alternative therapy in modern medicine (Song et al, 2021). Studies have shown that incorporations of TCEs into targeted rehabilitation for chronic low back pain (Wang et al, 2022), COPD (Ng et al, 2011), Parkinson's disease (Wang et al, 2021), and type 2 diabetes (Jia et al, 2021). Additionally, as a crucial component of cardiac rehabilitation, TCEs can improve fatigue, cardiorespiratory endurance, BP, and heart rate of CVD patients (Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As mind-body therapies that originated in China, TCEs play an important role in complementary and alternative therapy in modern medicine (Song et al, 2021). Studies have shown that incorporations of TCEs into targeted rehabilitation for chronic low back pain (Wang et al, 2022), COPD (Ng et al, 2011), Parkinson's disease (Wang et al, 2021), and type 2 diabetes (Jia et al, 2021). Additionally, as a crucial component of cardiac rehabilitation, TCEs can improve fatigue, cardiorespiratory endurance, BP, and heart rate of CVD patients (Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The procedure consisted of the collection of demographic information and administration of questionnaires and response inhibition tasks, which took about 1.5 h per participant. The questionnaires and behavioral tasks used in this study are the same as those used by Wang et al (2021) , which are part of the methodology in our published protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Three of them focused on frail older adults, including adults having a history of falls [21], a history of heart failure [22], and walking difficulty [17]. Some studied the effect on older adults with either anxiety disorder [29,31,35], depression [27,32,34,47], or both [44], while two of them targeted older adults suffering from insomnia and depression [36,39]. Six of the included studies studied the effect of cognition therapy on older adults suffering from dementia [28,30,38,41,45,49] ranging from mild to moderate dementia, vascular, Alzheimer's' or mixed.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Moreover, the outcomes of some of the studies support the efficacy of cognitive behavioral therapy in reducing insomnia, depression, and anxiety. The study Wang Z, et al [32] suggests that cognitive-existential group therapy with a picture of self and emphasis on training time and awareness of death in the elderly increased life expectancy reduced depression and improved the mental health of the elderly. Aerobic exercise is good not only for physical well-being but also for mental well-being.…”
Section: Mental Well-beingmentioning
confidence: 99%